A note on simulating the effect of monetary policy changes using only forward curves as inputs - Ansgar Rannenberg (National Bank of Belgium, 2025)
I show that in linear rational expectation models, the effect of a monetary tightening can be simulated using contemporaneous and anticipated monetary policy shocks that replicate the forward curves observed during the period of interest, normalized with the forward curve observed in the quarter before the tightening period of interest begins. In particular, the shocks in response to which the tightening occurs are irrelevant. All required information is incorporated in the normalized forward curves. I confirm this result via simulations and a formal proof. Then I use it to assess the effects of the recent monetary tightening in the Euro Area.
Keywords: E52; E43; 330; policy counterfactuals; monetary policy; interest rate expectations